Effectiveness of Self-Care Teaching Media for Pregnant Women and Pregnant Women with Hypertension - Rachmawati, Irma; Yanti Hermayanti; Ermiati, Ermiati (Jurnal Kesehatan, 2024)
Complications that occur during pregnancy are one of the causes of high maternal mortality, but these complications can be treated and prevented. Proper care before giving birth and adequate antenatal care can be supported by the presence of teaching media for pregnant women, including pregnant women with hypertension. Teaching media is effective in improving knowledge and self-care skills and helping understand pregnant women and pregnant women with hypertension. The small number of study articles on teaching media for self-care for pregnant women and pregnant women with hypertension made researchers interested in conducting a literature review on this topic. This study aims to determine the effectiveness of teaching media for self-care for pregnant women and pregnant women with hypertension. This research method is a literature review with a narrative review design. A comprehensive literature search was conducted using electronic databases, namely Pubmed, CINAHL, and Google Scholar. The author obtained 24 articles that were based on the research objectives. The results of the study, the teaching media used in self-care for pregnant women and pregnant women with hypertension are educational modules, power points, booklets, videos, animated videos, pamphlets, m-Health technology, mobile applications, social networks such as WhatsApp, Telegram, and Instagram. In conclusion, self-care teaching media can improve self-care in pregnant women, including pregnant women with hypertension because the teaching media is adjusted to the needs of pregnant women, the material is for self-care, the language is easy to understand, and the media used is interesting.